A Programming Tool for the Development of Parallel Computer Vision and Image Processing Algorithms and Applications - Bruno, Odemir Martinez; Costa, Luciano da Fontoura (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance Computing, 2001)
This article presents the development, implementation, and applications of the CVMP parallel programming tool for image processing and computer vision. Running on Borland Delphi and C++ Builder, this simple and easy-to-use tool incorporates visual programming and object oriented capabilities, having already allowed a series of applications and results, which are also outlined.